2023
DOI: 10.22441/sinergi.2023.3.015
|View full text |Cite
|
Sign up to set email alerts
|

Good Manufacturing Practice (GMP) in Tofu MSMEs in North Aceh

Cut Ita Erliana,
Iskandar Hasanuddin,
Yuwaldi Away
et al.

Abstract: This study examined tofu MSMEs in Lhokseumawe City and the North Aceh District. Observations indicate discrepancies between tofu production and the GMP requirements for Good Manufacturing Practices. The amount that the tofu sector has adopted appropriate food production procedures by the Regulation of the Ministry of Sector of the Republic of Indonesia Number 75/M-IND/PER/7/2010 is determined using a GMP approach. This research is anticipated to improve the product safety of the tofu industry and provide recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
1
0
0
Order By: Relevance
“…In line with other similar studies, the tofu manufacturing industry relies heavily on manual handling, which is associated with a higher risk of developing MSDs (Moradi and Barakt, 2020;Widodo et al, 2021;Erliana et al, 2023). This study found that the 12-month prevalence of MSDs among tofu factory workers was quite significant, where more than 50% of participants from traditional and silken tofu factories reported experiencing musculoskeletal pain in six body regions (lower back, right shoulder, neck, right wrist, left shoulder, and upper back) and three body regions (lower back, right shoulder, and upper back), respectively.…”
Section: Discussionsupporting
confidence: 82%
“…In line with other similar studies, the tofu manufacturing industry relies heavily on manual handling, which is associated with a higher risk of developing MSDs (Moradi and Barakt, 2020;Widodo et al, 2021;Erliana et al, 2023). This study found that the 12-month prevalence of MSDs among tofu factory workers was quite significant, where more than 50% of participants from traditional and silken tofu factories reported experiencing musculoskeletal pain in six body regions (lower back, right shoulder, neck, right wrist, left shoulder, and upper back) and three body regions (lower back, right shoulder, and upper back), respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Smart factory [44,57,58,54,44,59,60,40] 7. Smart maintenance [45,52,44,52,61,62,63,64] This paper fills the gaps in several previous studies regarding comparative studies of several major I4.0 indices or the development of instruments to measure Industry 4.0 readiness, focusing on technological characteristics. [41], information system and technology [7], implementation of the existing I4.0 index [29,34,35], and the I4.0 comparison, which focuses on the degree of readiness [22].…”
Section: Room For Improvementmentioning
confidence: 92%